Memahami Theory of Constraint dari Sumber Pertama Pembumian Kasus Novel “The Goals” - Alwan Sri Kustono (Jurnal Ekonomi Akuntansi dan Manajemen, 2019)
This article is grounded The Goal (Goldratt & Cox, 2008). It describes a case that occurred in a company. Manager has three months to change unprofitable and unreliable factory operations to succeed. It shows the differences that occur in a manufacturing company in a process, and how to discuss the difficulties that occur, and reduce their impact. Manager team discussed the challenges in the material flow, and immediately started requesting changes to help increase reserves and increase production. They brought an old machine that they received for free to increase the capacity of the engine, which has proven to be one of the two bottlenecks. Furthermore, they changed the process that happened to the company, changed like they did, which caused a great deal in getting the product and also caused some products to be heated several times to make it warmer and then even harder not just once or not at all. Keywords: throughput, bottleneck, performance, constraint